Êxtases do eu em um mundo dilacerado : uma análise estético-religiosa da poesia anjosiana - Bomfim, Luciana dos Santos (2019)
This dissertation presents an aesthetic-religious analysis of the poetry of Brazilian poet Augusto dos Anjos in his single work entitled Eu, based on Paul Tillich's theology of art. The research problematization starts with the characterization of the lyrical subject as a theme of itself, that is, a subject that, by assuming its lyric ecstatic condition, expresses the reality in which it is inserted and thus understands its existence in the world. The title Ecstasies of the self in a torn world: an aesthetic-religious analysis of Augusto dos Anjos’ poetry deals with this complex relationship between self and world in poetry, bringing up to the core of the question the dichotomy of language between subjectivity and objectivity as a vector of artistic creativity and hermeneutics of the human condition. The objective of the first chapter is to identify and describe Anjos’ work for the purpose of constructing and introducing the object of study through the poet's critical fortune and characterization of the lyrical subject in Anjos. Through defined theoretical references, the second chapter establishes the mediations for the aesthetic-religious analysis of Anjos’ poetry in relation to Paul Tillich’s theology of art. Finally, in the third chapter, we present an analysis of selected poems of Eu in the light of the relation between theology and literature from the perspective of the proposed problematization. In the face of the presented objectives, therefore, we propose that Anjos’ poetry be understood as a cultural production that accomplishes a symbolic mediation between the existence and the real and, through this relation, allows the poetic fulfilling and expression of what Tillich defines as unconditionality of meaning.